KONTRIBUSI DAKWAH DALAM AKTUALISASI NILAI-NILAI EKONOMI ISLAM PADA MASYARAKAT MELAYU PEDESAAN - Ginda Harahap (Jurnal Dakwah Risalah, 2019)
The role of dakwah nowadays strategically supports the actualization of Islamic economy values in Malay society. Dakwah is aplicable activity in persuading, calling,and motivating muslims to implement Islamic teaching in daily life. This research was conducted to obtain information about the positive contribution of dakwah activities as an instrument of Islamization in the inheritance of the Islamic economic values of the Rokan Hulu Malay ethnic group, and its application in economic transactions in contemporary Malay society. The study was conducted in Rambah District, where 90% of the majority was Malay ethnic. This research used quantitative approach by spreading quetioners in collecting data. The data analysis technique used Contingency Coefficient Correlation. Based on the results of the analysis it was found that there was contribution of da'wah activities in effort to actualize Islamic economic values but it is not significant.